Swift Follow-Up of IceCube Triggers, and Implications for the Advanced-LIGO Era - Evans, P. A.; Osborne, J. P.; Kennea, J. A.; Smith, M.; Palmer, D. M.; Gehrels, N.; Gelbord, J. M.; Homeier, A.; Voge, M.; Strotjohann, N. L.; Cowen, D. F.; Boser, S.; et al. (Monthly notices of the Royal Astronomical Society, 2015)
Between 2011 March and 2014 August Swift responded to 20 triggers from the IceCube neutrino observatory, observing the IceCube 50 per cent confidence error circle in X-rays, typically within 5 h of the trigger. No confirmed counterpart has been detected. We describe the Swift follow-up strategy and data analysis and present the results of the campaign. We discuss the challenges of distinguishing the X-ray counterpart to a neutrino trigger from serendipitous uncatalogued X-ray sources in the error circle, and consider the implications of our results for future strategies for multimessenger astronomy, with particular reference to the follow-up of gravitational wave triggers from the advanced-era detectors.